Impact assessment of the three gorges reservoir on the contribution rate for diversion through the three outlets. Issue 1 (December 2020) - Chen, M F; Li, Y T; Li, A Q; Yao, W
Abstract: The Dongting Lake distributes water and sediment of the Yangtze River through the three outlets. Influencing factors of the diversion capacity are complicated. In order to evaluate the influences of the operation of the Three Gorges Reservoir (TGR) on the diversion of the three outlets, this paper investigates systematically the variation process of the runoff at the three outlets based on substantially raw data and principles of variable control. By using comparative analysis and the calculation method of runoff reduction, the change magnitude of the runoff at the three outlets in different periods were quantified and the contribution rates of different influencing factors were estimated. Results show that (1) Inflow difference from the Yangtze River is the primary factor causing the runoff reduction of the three outlets. After the operation of TGR, the Yangtze River was in dry years. Therefore, over 60% of runoff reduction can be attributed to the variation of natural inflow discharge. (2) As the flow is retained by TGR, the runoff of the three outlets further reduced. From 2003-2008, the contribution rates of natural flow, sediment trapping and reservoir regulation to the runoff reduction at the three outlets were 76.19%, 13.49%, 10.32%, while their counterparts after optimal operation of TGR became 66.05%, 14.20% and 19.75% respectively. (3) Reservoir operation after the flood season showed the most significant impact on runoff of the three outlets, resulting in an increase in the number of shut-off days of the three-distributary channels from September to October, especially at Shadaoguan and Kangjiagang.